The combined effect of technological relatedness and knowledge utilization on explorative and exploitative invention performance post-M & A. Issue 2 (9th May 2016) - Ganzaroli, Andrea; De Noni, Ivan; Orsi, Luigi; Belussi, Fiorenza
Abstract : Purpose: – The purpose of this paper is to investigate the combined effect of Mergers and Acquisitions (M & A) partners' technological relatedness and the acquirer's effective utilization of the target's knowledge on explorative and exploitative invention performance post-M & A. Design/methodology/approach: – Based on the knowledge perspective of an M & A, this study measures how much of the target's knowledge acquired in an M & A has been effectively transformed into new knowledge. A negative binomial regression on a cross-sectional data set of 152 bio-pharmaceutical firms (59 European firms and 93 North American firms) completing at least one M & A in the period between 2001 and 2005 is conducted. The effect of knowledge utilization is assessed by comparing performance six years before the M & A and six years after. Findings: – The effective assimilation and utilization of acquired knowledge positively affects both acquirers' explorative and exploitative performance post-M & As. The combined effect with technological relatedness, measured as similarity and complementarity, further enhances the acquirer's technological performance. However, while the utilization of similar knowledge significantly affects only exploitative invention performance, the utilization of complementary knowledge influences both, although explorative more than exploitative performance. Originality/value: – The acquirer's ability to effectively use the target's knowledge is crucial in order to support the transformation of the inventive potential, such as is embodied in the interaction between an internal and an external base of knowledge, into new explorative and exploitative performance.